Contribution of bone marrow‐derived mesenchymal stem cells to the morphological changes in the bladder after partial outlet obstruction: A preliminary study. (3rd March 2014) - Kanno, Yukiko; Mitsui, Takahiko; Sano, Hiroshi; Kitta, Takeya; Moriya, Kimihiko; Nonomura, Katsuya
<x xml:space="preserve">Abstract</x> Objectives To investigate the contribution of bone marrow‐derived mesenchymal stem cells to the changes in bladder morphology in response to partial bladder outlet obstruction. Methods Allogenic bone marrow cells were transplanted from transgenic rats expressing green fluorescent protein into female Sprague–Dawley rats 1 day after their bone marrow‐derived mesenchymal stem cells had been destroyed by irradiation. This generated chimeric rats in which green fluorescent protein labeled bone marrow‐derived mesenchymal stem cells replaced host bone marrow‐derived mesenchymal stem cells. The animals received partial bladder outlet obstruction or sham surgery 6 weeks later. The animals were killed 6 weeks after the surgery, and bladder tissue was prepared for immunofluorescence with antibodies against a urothelium marker (AE1/AE3), a myofibroblast marker (vimentin), a smooth muscle marker and green fluorescent protein. Results More labeled bone marrow‐derived mesenchymal stem cells were found in the partial bladder outlet obstruction group than in the in the sham group. Most bone marrow‐derived mesenchymal stem cells were present around the basement membrane (laminin) and lamina propria below the urothelium. Bone marrow‐derived mesenchymal stem cells were also found in the urothelium layer, and some of them were double‐stained with green fluorescent protein and AE1/AE3. Some bone marrow‐derived mesenchymal stem cells, which were located in the interstitial tissue, were double‐stained with green fluorescent protein and vimentin. Bone marrow‐derived mesenchymal stem cells, which migrated into the smooth muscle layer, showed fusiform morphology, and some were double‐stained with green fluorescent protein and smooth muscle marker. Conclusions Bone marrow‐derived mesenchymal stem cells home to the partial bladder outlet obstruction bladder, and these cells have the potential to differentiate into the several components of bladder tissue including the urothelium, myofibroblasts and smooth muscle cells. Thus, bone marrow‐derived mesenchymal stem cells contribute to the morphological changes of the bladder in response to partial bladder outlet obstruction.